Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \({\cos ^2}\alpha + {\sin ^2}\alpha = 1\)
b) \(\tan \alpha .\cot \alpha = \frac{{\sin \alpha }}{{\cos \alpha }}.\frac{{\cos \alpha }}{{\sin \alpha }} = 1\)
c) \(\frac{{{{\sin }^2}\alpha + {{\cos }^2}\alpha }}{{{{\cos }^2}\alpha }} = \frac{{{{\sin }^2}\alpha }}{{{{\cos }^2}\alpha }} + \frac{{{{\cos }^2}\alpha }}{{{{\cos }^2}\alpha }} = {\tan ^2}\alpha + 1\)
d) \(\frac{1}{{{{\sin }^2}\alpha }} = \frac{{{{\sin }^2}\alpha + {{\cos }^2}\alpha }}{{{{\sin }^2}\alpha }} = \frac{{{{\sin }^2}\alpha }}{{{{\sin }^2}\alpha }} + \frac{{{{\cos }^2}\alpha }}{{{{\sin }^2}\alpha }} = 1 + {\cot ^2}\alpha \)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có \sin 5\alpha -2\sin \alpha \left({\cos} 4\alpha +\cos 2\alpha \right)=\sin 5\alpha -2\sin \alpha .\cos 4\alpha -2\sin \alpha .\cos 2\alphasin5α−2sinα(cos4α+cos2α)=sin5α−2sinα.cos4α−2sinα.cos2α
=\sin 5\alpha -\left(\sin 5\alpha -\sin 3\alpha \right)-\left(\sin 3\alpha -\sin \alpha \right)=sin5α−(sin5α−sin3α)−(sin3α−sinα)
=\sin \alpha .=sinα.
Vậy \sin 5\alpha -2\sin \alpha \left({\cos} 4\alpha +\cos 2\alpha \right)=\sin \alphasin5α−2sinα(cos4α+cos2α)=sinα
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(cot\alpha=\sqrt[]{5}\Rightarrow tan\alpha=\dfrac{1}{\sqrt[]{5}}\)
\(C=sin^2\alpha-sin\alpha.cos\alpha+cos^2\alpha\)
\(\Leftrightarrow C=\dfrac{1}{cos^2\alpha}\left(tan^2\alpha-tan\alpha+1\right)\)
\(\Leftrightarrow C=\left(1+tan^2\alpha\right)\left(tan^2\alpha-tan\alpha+1\right)\)
\(\Leftrightarrow C=\left(1+\dfrac{1}{5}\right)\left(\dfrac{1}{5}-\dfrac{1}{\sqrt[]{5}}+1\right)\)
\(\Leftrightarrow C=\dfrac{6}{5}\left(\dfrac{6}{5}-\dfrac{\sqrt[]{5}}{5}\right)=\dfrac{6}{25}\left(6-\sqrt[]{5}\right)\)
1: \(cota=\sqrt{5}\)
=>\(cosa=\sqrt{5}\cdot sina\)
\(1+cot^2a=\dfrac{1}{sin^2a}\)
=>\(\dfrac{1}{sin^2a}=1+5=6\)
=>\(sin^2a=\dfrac{1}{6}\)
\(C=sin^2a-sina\cdot\sqrt{5}\cdot sina+\left(\sqrt{5}\cdot sina\right)^2\)
\(=sin^2a\left(1-\sqrt{5}+5\right)=\dfrac{1}{6}\cdot\left(6-\sqrt{5}\right)\)
2: tan a=3
=>sin a=3*cosa
\(1+tan^2a=\dfrac{1}{cos^2a}\)
=>\(\dfrac{1}{cos^2a}=1+9=10\)
=>\(cos^2a=\dfrac{1}{10}\)
\(B=\dfrac{3\cdot cosa-cosa}{27\cdot cos^3a+3\cdot cos^3a+2\cdot3\cdot cosa}\)
\(=\dfrac{2\cdot cosa}{30cos^3a+6cosa}=\dfrac{2}{30cos^2a+6}\)
\(=\dfrac{2}{3+6}=\dfrac{2}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Có \(sin\alpha+cos\alpha=\dfrac{2}{5}\Leftrightarrow\left(sin\alpha+cos\alpha\right)^2=\dfrac{4}{25}\)
\(\Leftrightarrow sin^2\alpha+2sin\alpha\cdot cos\alpha+cos^2\alpha=\dfrac{4}{25}\)
\(\Leftrightarrow\left(sin^2\alpha+cos^2\alpha\right)+2sin\alpha\cdot cos\alpha=\dfrac{4}{25}\)
\(\Leftrightarrow1+2sin\alpha\cdot cos\alpha=\dfrac{4}{25}\Leftrightarrow sin\alpha\cdot cos\alpha=-\dfrac{21}{50}\)
Ta có:
\(P=sin^3\alpha+cos^3\alpha=\left(sin\alpha+cos\alpha\right)\left(sin^2\alpha-sin\alpha\cdot cos\alpha+cos^2\alpha\right)\)
\(=2\left[1-\left(-\dfrac{21}{50}\right)\right]=\dfrac{71}{25}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(P=\frac{sina+cosa}{sina-cosa}=\frac{\frac{sina}{sina}+\frac{cosa}{sina}}{\frac{sina}{sina}-\frac{cosa}{sina}}=\frac{1+cota}{1-cota}=\frac{1+2}{1-2}=-3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(VT=\dfrac{\left(sina+cosa\right)^3-3\cdot sina\cdot cosa\left(sina+cosa\right)}{sina+cosa}\)
=(sina+cosa)^2-3*sina*cosa
=sin^2a+cos^2a-sina*cosa
=1-sina*cosa=VP
c: VT=(sin^2a+cos^2a)^2-2*sin^2a*cos^2a-(sin^2a+cos^2a)^3+3*sin^2a*cos^2a*(sin^2a+cos^2a)
=1-2sin^2a*cos^2a-1+3*sin^2a*cos^2a
=sin^2a*cos^2a=VP
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \({\left( {\sin \alpha + \cos \alpha } \right)^2} = {\sin ^2}\alpha + 2\sin \alpha \cos \alpha + {\cos ^2}\alpha = 1 + \sin 2\alpha \;\)
b) \({\cos ^4}\alpha - {\sin ^4}\alpha = \left( {{{\cos }^2}\alpha - {{\sin }^2}\alpha } \right)\left( {{{\cos }^2}\alpha + {{\sin }^2}\alpha } \right) = \cos 2\alpha \;\)
\(-cosa+sin\frac{a}{2}=0\)
\(\Leftrightarrow cosa=sin\frac{a}{2}\)
\(\Leftrightarrow cosa=cos\left(\frac{\pi}{2}-\frac{a}{2}\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}a=\frac{\pi}{2}-\frac{a}{2}+k2\pi\\a=\frac{a}{2}-\frac{\pi}{2}+k2\pi\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}a=\frac{\pi}{3}+\frac{k4\pi}{3}\\a=-\pi+k4\pi\end{matrix}\right.\)